Studies on the Assessment of Toxic Metals Present in Biological Samples (Part-1) - Kulshrestha Shail; Awasthi Alok; Dabral S. K. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Development in the 20th century has brought social and economic benefits to us but the changes have also caused a wide range of environmental problems at both local and global level. Increased industrial activities has increased the incidence of percolation of toxic metal ions to the soil and water bodies and presently their presence in ecosystem, have reached to an alarming level that whole planet and entire humanity is at stake. The toxic metals have a great tendency of bioaccumulation through which they enter the food chain system and ultimately affect adversely the life in various ways. Further, due to contamination of irrigation system by the harmful and deleterious Chemicals and toxic metals, the toxic metals have found their ways through the aquatic systems and soil to the farm products, food grains, vegetables, fruits, and even milk. In continuation of our efforts to find out the toxic metals in the ecosystem, this communication describes the estimation of the metal contents in various samples of summer vegetables and fruits collected from the agriculture fields near the bank of the River Ganges from Rishikesh onwards to Garhmukteshwer. For the sake of comparison, the samples of soil and water used by villagers for irrigation purpose were also analyzed for these metals.